К функциональному анализу относительной длины отделов позвоночника некоторых куньих (Mammalia, Mustelidae) - Пилипчук, О.Я. (Вестник зоологии, 1979)
The absolute lengths of curvical tharacic, lumbar and sacral spines were measured and then their relative lengths (in % to the total length) were calculated for certain mustelids, (51 skeletons of B species were examined). The data of the investigation characterize the biomechanics peculiarities of the locomotor apparatus in the animals under study.